The coexistence of the “Rome II” Regulation and the 1971 Hague Convention on Road Traffic Accidents in Spanish judicial practice - Goñi Urriza, Natividad (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The concurrence of applicable rules in litigation related to road traffic accidents (Rome II Regulation and 1997 Hague Convention) in Spain terribly complicates the determination of the applicable law. In Spanish judicial practice there are many examples of errors in the identification of the applicable conflict rule because the scope of application of each of the allegedly concurrent rules is not analyzed. The solution to the regulatory concurrence in Rome II Regulation does not help predictability in the matter of determining the state law that will govern the disputed issue, quite the contrary, it encourages forum shopping